DNA Methylation of TLR4, VEGFA, and DEFA5 Is Associated With Necrotizing Enterocolitis in Preterm Infants - Klerk, Daphne H.; Plösch, Torsten; Verkaik-Schakel, Rikst Nynke; Hulscher, Jan B. F.; Kooi, Elisabeth M. W.; Bos, Arend F. (Frontiers in Pediatrics, 2021)
Background: Epigenetic changes, such as DNA methylation, may contribute to an increased susceptibility for developing necrotizing enterocolitis (NEC) in preterm infants. We assessed DNA methylation in five NEC-associated genes, selected from literature: EPO, VEGFA, ENOS, DEFA5 and TLR4 in infants with NEC and controls. Methods: Observational cohort study including 24 preterm infants who developed NEC ( Bell Stage IIA) and 45 matched controls. DNA was isolated from stool samples and methylation measured using pyrosequencing. We investigated differences in methylation prior to NEC compared with controls. Next, in NEC infants, we investigated methylation patterns long before, a short time before NEC onset, and after NEC. Results: Prior to NEC, only TLR4 CpG 2 methylation was increased in NEC infants (median=75.4%, IQR=71.3%–83.8%) versus controls (median=69.0%, IQR= 64.5%–77.4%, p=0.025). In NEC infants, VEGFA CpG 3 methylation was 0.8% long before NEC, increasing to 1.8% a short time before NEC and 2.0% after NEC (p=0.011; p=0.021, respectively). A similar pattern was found in DEFA5 CpG 1, which increased from 75.4% to 81.4% and remained 85.3% (p=0.027; p=0.019, respectively). These changes were not present for EPO, ENOS and TLR4. Conclusion: Epigenetic changes of TLR4, VEGFA and DEFA5 are present in NEC infants and can differ in relation to the time of NEC onset. Differences in DNA methylation of TLR4, VEGFA and DEFA5 may influence gene expression and increase the risk for developing NEC. This study also demonstrates the use of human DNA extraction from stool samples as a novel non-invasive method for exploring the bowel of preterm infants and which can also be used for necrotizing enterocolitis patients.